2010
DOI: 10.1016/j.cardfail.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil Gelatinase-Associated Lipocalin (NGAL) in Predicting Worsening Renal Function in Acute Decompensated Heart Failure

Abstract: Background The development of worsening renal function (WRF, defined as creatinine rise ≥0.3 mg/dL) occurs frequently in the setting of acute decompensated heart failure (ADHF) and strongly predicts adverse clinical outcomes. Neutrophil gelatinase–associated lipocalin (NGAL) is produced by the nephron in response to tubular epithelial damage and serves as an early marker for acute renal tubular injury. We sought to determine the relationship between admission serum NGAL levels and WRF in the setting of ADHF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
4
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(168 citation statements)
references
References 16 publications
10
140
4
14
Order By: Relevance
“…In the present study the higher NGAL level, and the correlations between NGAL and other kidney parameters were studied (results and fig. 1-6) and are in agreement with many reports, which implies that NGAL is an early indicator biomarker for both RT and advanced CKD patients and can be used to start early treatment in these patients [39][40][41][42]. Malyszko et al in their study showed that in patients with delayed graft function; there was no fall in serum NGAL or cystatin-c.…”
Section: Resultssupporting
confidence: 84%
“…In the present study the higher NGAL level, and the correlations between NGAL and other kidney parameters were studied (results and fig. 1-6) and are in agreement with many reports, which implies that NGAL is an early indicator biomarker for both RT and advanced CKD patients and can be used to start early treatment in these patients [39][40][41][42]. Malyszko et al in their study showed that in patients with delayed graft function; there was no fall in serum NGAL or cystatin-c.…”
Section: Resultssupporting
confidence: 84%
“…No patient with Ͻ170-ng/ml first-morning NGAL developed type 1 cardio-renal syndrome, and half of the patients with a first-morning value Ͼ170 ng/ml develop type 1 cardiorenal syndrome. The association of higher serum NGAL levels with worsening renal function was already demonstrated by Aghel et al in a population of 91 acute HF patients (17). Different from the latter study in which worsening renal function was considered from the 5th day onward, we restricted type 1 cardio-renal syndrome to the first 48 to 72 hours of admission.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 Though, a few studies question the role of NGAL in predicting the risk of AKI, serum NGAL was used as a marker for AKI, and it was also shown to be associated with a higher risk of AKI at different cut-off levels. 21,22 Acute decompensated HF patients with serum NGAL levels over 167.5 ng/mL had 2.7 times increased mortality and 2.9 times increased hospitalization rates. 23 Alvelos et al defined a cut-off value of 170 ng/mL for serum NGAL to foresee type 1 CRS with 100% sensitivity and 86.7% specificity (AUC was 0.93).…”
Section: Discussionmentioning
confidence: 99%